2020
DOI: 10.1002/advs.202001802
|View full text |Cite
|
Sign up to set email alerts
|

Fast Permeation of Small Ions in Carbon Nanotubes

Abstract: Simulations and experiments have revealed enormous transport rates through carbon nanotube (CNT) channels when a pressure gradient drives fluid flow, but comparatively little attention has been given to concentration‐driven transport despite its importance in many fields. Here, membranes are fabricated with a known number of single‐walled CNTs as fluid transport pathways to precisely quantify the diffusive flow through CNTs. Contrary to early experimental studies that assumed bulk or hindered diffusion, measur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
31
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(31 citation statements)
references
References 51 publications
0
31
0
Order By: Relevance
“…For instance, numerous experiments and molecular dynamics (MD) simulations revealed that nanoconfined water may freeze into various one-dimensional (1D) and two-dimensional (2D) polymorphous and polyamorphous structures at low temperatures 4,8,10,[16][17][18][19][20][21][22][23][24][25][26][27][28][29] . Fast mass transport and high proton conductivity were also observed for water confined inside nanotubes 2,7,30 . Notably, previous computational and experimental studies demonstrated that the static dielectric constant of water can exhibit marked decrease under strongly confined conditions [31][32][33] , which may induce unusual behaviors of ions in the strongly confined water.…”
mentioning
confidence: 81%
See 2 more Smart Citations
“…For instance, numerous experiments and molecular dynamics (MD) simulations revealed that nanoconfined water may freeze into various one-dimensional (1D) and two-dimensional (2D) polymorphous and polyamorphous structures at low temperatures 4,8,10,[16][17][18][19][20][21][22][23][24][25][26][27][28][29] . Fast mass transport and high proton conductivity were also observed for water confined inside nanotubes 2,7,30 . Notably, previous computational and experimental studies demonstrated that the static dielectric constant of water can exhibit marked decrease under strongly confined conditions [31][32][33] , which may induce unusual behaviors of ions in the strongly confined water.…”
mentioning
confidence: 81%
“…A queous solutions under nanoscale confinement have attracted considerable interest over the past few years, owing to their unusual structural, dynamical, and physicochemical properties (different from those of their bulk counterparts), as well as to their broad significance for nanoscale chemical, biological, and physical systems such as ion channels/ batteries and water desalination [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15] . For instance, numerous experiments and molecular dynamics (MD) simulations revealed that nanoconfined water may freeze into various one-dimensional (1D) and two-dimensional (2D) polymorphous and polyamorphous structures at low temperatures 4,8,10,[16][17][18][19][20][21][22][23][24][25][26][27][28][29] .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Certain aspects of such pores can be effectively mimicked by simple non-biological structures, for example graphene nanopores and metal-organic structures (2). Carbon nanotubes (CNTs) are also particularly attractive as structural templates because they can imitate many fundamental aspects of such pores including high transport efficiency, tunable pore diameters, functionalization, and well-defined hydrophobic interiors (45)(46)(47)(48)(49)(50). The relevant properties of CNT nanopores have been extensively studied, both experimentally and with simulations (49,(51)(52)(53).…”
Section: It Has Been Suggested Bymentioning
confidence: 99%
“…Owing to the introduction of nanochannel structures in the desired membranes, selective ion separation can be achieved by mediating the nanochannel shape and size, charge, wettability, and specific recognition of the nanochannel walls. Membranes such as 1D CNTs [114,280] and polyhydrazide nanotubes, [281] 2D layered GO, [61,282,283] MOFs, [60,154,284] and COFs [58] consisting of interconnected and uniform pores and ultrathin [285] and sandwich-like structures [38] have been used for controllable ion sieving. For instance, stacked graphene and GO membranes with sub-nanometer interlayer spacing showed selective transport of alkali and alkaline earth cations across the membrane owing to the synergistic effect of cation-π interactions and ion dehydration.…”
Section:  Ion Separationmentioning
confidence: 99%